(untitled) (Research, Society and Development, 2020)
Scientific research on arterial hypertension shows that there are still many gaps regarding risk factors associated with the work environment. Stress is one of the factors capable of raising blood pressure, and a stressful work environment can be extremely harmful to the worker, leading to a state in which wear and tear of the human organism occurs and decreased work capacity. It is based on a qualitative approach carried out through bibliographic research based on several authors. For the construction of the body of the study, a search was carried out in the electronic database: VHL Regional Portal (Virtual Health Library) with selection of the databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) with the descriptors: hypertension, work and risk factors. When compared, related studies have shown that there is a need to investigate the health of workers in general, regarding the issue of arterial hypertension related to risk factors at work. It is concluded that occupational stress is one of the problems that most affects the worker in the work environment, stress that when exaggerated ends up affecting both physical and mental health leading society to get high blood pressure.